The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6404/ab7c6b
|View full text |Cite
|
Sign up to set email alerts
|

Teaching labs for blind students: equipment to measure the thermal expansion coefficient of a metal

Abstract: We design a Teaching laboratory experience for blind students, to measure the linear thermal expansion coefficient of an object. We use an open-source electronic prototyping platform to create interactive electronic objects, with the conversion of visual signals into acoustic signals that allow a blind student to participate at the same time as their classmates in the laboratory session. For the student it was the first time he managed to participate normally in a physics laboratory. PACS numbers: 05.30.Ch,05.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…La adaptación no solo está enfocada al uso del sistema braille, sino a cambios en el currículo que lleven a los estudiantes a desarrollar otras capacidades para proponer nuevas actividades en el aula, tanto de forma teórica como práctica. En este orden de ideas, se tienen lineamientos, materiales de clase y software que facilitan las condiciones de trabajo (Negrete et al, 2020), planes de estudios que incluyen las percepciones de los estudiantes ciegos (Holt et al, 2019), ciclos de aprendizaje (Azevedo y Santos, 2014a), uso de herramientas que permitan representar los diferentes diagramas, tablas o información de los libros de texto mediante modelos 3D y de alto relieve (Dickman et al, 2014;Torres y Mendes, 2017;Toenders et al, 2017b), empleo de videos o audios descriptivos (Cozendey y Costa, 2016), adaptación de material de laboratorio como termómetros (Silva y Santos, 2018), y realización de maquetas y modelos físicos (Goncalves et al, 2017).…”
Section: Discusión De Los Resultadosunclassified
“…La adaptación no solo está enfocada al uso del sistema braille, sino a cambios en el currículo que lleven a los estudiantes a desarrollar otras capacidades para proponer nuevas actividades en el aula, tanto de forma teórica como práctica. En este orden de ideas, se tienen lineamientos, materiales de clase y software que facilitan las condiciones de trabajo (Negrete et al, 2020), planes de estudios que incluyen las percepciones de los estudiantes ciegos (Holt et al, 2019), ciclos de aprendizaje (Azevedo y Santos, 2014a), uso de herramientas que permitan representar los diferentes diagramas, tablas o información de los libros de texto mediante modelos 3D y de alto relieve (Dickman et al, 2014;Torres y Mendes, 2017;Toenders et al, 2017b), empleo de videos o audios descriptivos (Cozendey y Costa, 2016), adaptación de material de laboratorio como termómetros (Silva y Santos, 2018), y realización de maquetas y modelos físicos (Goncalves et al, 2017).…”
Section: Discusión De Los Resultadosunclassified
“…In our Physics department, we have had previous experiences teaching blind students. For instance, we have adapted experiments to measure the linear expansion coefficient 23 and the distance between nodes in standing waves 24 . These adaptations have attracted the interest of blind students to apply to our university.…”
Section: Introductionmentioning
confidence: 99%
“…Technology usage has been introduced with the Expanded Core Curriculum, and the use of assistive technology has been shown to be highly effective with VI students in accessing information and in the pursuit of an independent daily life (Altunay Arslantekin, 2012; Yalcin & Altunay Arslantekin, 2019). Studies in the literature support the effectiveness of assistive technology application in teaching science and mathematics since it ensures the active participation of students with VI in classes (da Mota Silveira & Martini, 2017;Koehler, Wild, & Tikkun, 2018;Ludi, Canter, Ellis, & Shrestha, 2012;Lunney, 1995;Nees & Berry, 2013;Negrete, Lisboa, Peña, Dib, & Vargas, 2020;Supalo, Humphrey, Mallouk, Wohlers, & Carlsen, 2016). Supalo et al (2016) reported that students with VI can effectively participate in technologysupported science laboratories.…”
Section: Introductionmentioning
confidence: 99%